Study on Optical Features of Circular Photonic Crystal Fibers with Various Air-hole Size - Van Trong, Dang; Tran Bao Tran, Le; Van Lanh, Chu; Thi Hong Phuong, Nguyen; Trang, Nguyen Minh Hang; Trong Duc, Hoang; Thi Thuy, Nguyen (VNU Journal of Science: Mathematics - Physics, 2022)
: In this workwe proposed a newly designed photonic crystal fiber (PCF) with a circular lattice, the difference between the air-hole diameters of the first ring and the other rings makes it possible to improve the nonlinear properties of fibers.  We investigated the effect of varying the filling factor ( d 1 /Ʌ ) and lattice constant ( Ʌ ) on the nonlinear characteristics of photonic crystal fibers in the 0.5 - 2 µm wavelength range. The advantages of these photonic crystal fibers are the flat and near-zero dispersion, low attenuation, and high nonlinear coefficient. From simulation results, we have selected three optimal structures ( Ʌ = 1.0 μm; d 1 /Ʌ = 0.4, Ʌ = 0.8 μm; d 1 /Ʌ = 0.6, and Ʌ = 0.8 μm; d 1 /Ʌ = 0.65) to analyze the nonlinear characteristics at the pump wavelengths. The proposed fibers are valuable for supercontinuum generation. Keywords: